Apparent disapperance of hypernatraemic dehydration from infant deaths in Sheffield. Issue 6190 (8th September 1979) - Sunderland, R; Emery, J L
Abstract : The death certificates and necropsy reports of the 1115 Sheffield infants who died under 2 years of age in 1969-78 were examined. This study showed the apparent disappearance of deaths with hypernatraemia and in particular deaths presenting as cot deaths. The fall in incidence may be as much the result of an intensive local campaign on child care and infant feeding as of the change in the composition of dried milk for baby feeding.